HETEROSIS AND PROPORTIONAL CONTRIBUTION OF LINE × TESTER INTERACTION AND GENE ACTION IN DIFFERENT MAIZE HYBRIDS UNDER WATER REGIMES - I. R. Noorka; Taufiqullah (Journal of Animal and Plant Sciences, 2015)
The project is based on line × tester analysis to study the heterosis, proportional contribution of line, testers and line × tester interaction and gene action in cross combinations of diverse maize genotypes under normal irrigation and water stress conditions. Twelve parents comprised of eight inbred lines as females and four as male; were crossed to produce 32 F1 hybrids. Parents along with their hybrids were evaluated in Completely Randomized Design (CRD) with three replications in two seasons. The heterotic value, proportional contribution of Lines, Testers and Line × Tester interaction and gene action was studied for the characters i.e. plant height, leaf area per plant, kernels per row, ear length, ear diameter, grain yield per plant and harvest index. Variable heterosis both in magnitude and direction was evident. Non-additive gene effects were observed for plant height, kernels per rows, ear length, ear diameter, grain yield per plant and harvest index for successful breeding programme.
Keywords: Maize; Water stress; Line × tester; Heterosis; Gene Action; Additive; Susceptible